2001
DOI: 10.1210/mend.15.10.0708
|View full text |Cite
|
Sign up to set email alerts
|

New Androgen Response Elements in the Murine Pem Promoter Mediate Selective Transactivation

Abstract: The Pem homeobox transcription factor is expressed under androgen control in the testis and epididymis. It is also transcribed in the ovary, muscle, and placenta. The mouse Pem gene promoter was cloned and sequenced. It was analyzed in transactivation tests using CV-1 and PC-3 cells expressing the AR and found to be strongly stimulated by androgens. EMSAs and mutational analysis of the Pem promoter allowed the identification of two functional androgen response elements named ARE-1 and ARE-2. They both differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…1B, WT). Cells incubated without R1881 and the AR expression plasmid expressed only low levels of luciferase from the Pp reporter vector (only slightly above that of pRL-null), consistent with earlier studies showing that the Pp depends on AR and androgen for expression (3,39,51). To assess whether AR might directly regulate the Pp, we scanned the 0.6-kb Pp 5Ј flanking region for sequences conforming to consensus ARbinding sites (androgen-response elements, or AREs) (57).…”
Section: Identification Of Ares Essential For Rhox5 Pp Transcription supporting
confidence: 80%
See 1 more Smart Citation
“…1B, WT). Cells incubated without R1881 and the AR expression plasmid expressed only low levels of luciferase from the Pp reporter vector (only slightly above that of pRL-null), consistent with earlier studies showing that the Pp depends on AR and androgen for expression (3,39,51). To assess whether AR might directly regulate the Pp, we scanned the 0.6-kb Pp 5Ј flanking region for sequences conforming to consensus ARbinding sites (androgen-response elements, or AREs) (57).…”
Section: Identification Of Ares Essential For Rhox5 Pp Transcription supporting
confidence: 80%
“…Rhox5 is one of very few genes known to be directly regulated by AR in Sertoli cells and, to our knowledge, is the only known androgen-induced transcription factor gene expressed in Sertoli cells (41). Interestingly, its Pp harbors "selective" AREs that respond to AR and not other nuclear hormone receptors, based on studies in cell lines (3) and a knock-in mouse that expresses a form of AR only able to activate the transcription of promoters harboring "nonselective" AREs (56). Recently, we discovered that a subset of other Rhox genes is induced by androgen and AR in the MSC1 cell line (39); most of these genes also depend on AR in Sertoli cells for their expression in testes in vivo (our unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion comes from several lines of evidence, including: i) Rhox5 mRNA levels (measured with either Rhox5 or Pp-specific probes) are dramatically reduced in animals deficient in the ability to produce LH (the peptide hormone responsible for inducing testosterone production in Leydig cells) as a result of hypophysectomy, chemical treatment, or genetic mutations , 1996c, Maiti et al 1996a, Sutton et al 1998; ii) testosterone reverses the defect in Rhox5 expression caused by loss of LH , Sutton et al 1998; and ix) the Pp possesses four androgen-response elements (AREs), each of which is required for its AR-and androgen-dependent expression in transfected cell lines (Barbulescu et al 2001, Geserick et al 2003, Bhardwaj et al 2008, Faus & Haendler 2008. Together, these studies strongly suggest that the Rhox5 Pp is a direct target of AR in Sertoli cells.…”
Section: The Ppmentioning
confidence: 99%
“…Purified, recombinant A-NTD-DBD was diluted to a final concentration of 40 pmole/20 µl reaction in 10 EMSA buffer, 20% glycerol and 0·25 µg/ml polyd [I-C] in the presence or absence of 60 pmoles DNA (C3(1) or (1) represents the androgen receptor binding site identified within the first intron (+1359) of the C3 subunit of the prostatic binding protein (prostain) (Claessens et al 1989); PbARE2 is the androgen receptor selective response element identified and characterised in the 58-flanking sequence (−140 to −117) of the rat probasin gene (Rennie et al 1993, Claessens et al 1996; MMTV represents a hormone response element (HRE) derived from the mouse mammary tumour virus long terminal repeat (Parker et al 1987); ARE1 was identified as an androgen receptor selective response element in the promoter (−85 to −69) of the PEM homeobox transcription factor gene (Barbulescu et al 2001); IDR17, is an artificial response element selected from a partially-degenerate pool of oligonucleotides, that contains both direct and inverted half-site motifs (Zhou et al 1997). Response element half-sites are shown in bold type.…”
Section: Proteolysismentioning
confidence: 99%